Study on Fatigue Performance of Nylon Worm Gear Under Multiple Working Condition based on RecurDyn - Jianfei Chen; Fan Yang; Shulin Wang (Jixie chuandong)
The main failure mode in automobile steering system is the bending fatigue failure of the tooth root of nylon worm gear， based on Hertz contact theory and incremental finite element method based on corotational coordinate method， the worm and worm gear nonlinear transient dynamics model is built in multibody dynamics software RecurDyn， and according to the test requirements of loading conditions， the stress analysis and fatigue life analysis is carried out in the software， the nylon worm gear tooth root in each loading condition of transient stress value can be accurately got， then the nylon worm gear fatigue life in the corresponding time process is studied. Fatigue life analysis of the simulation analysis and experimental show that when the dynamics model and fatigue damage model meet certain accuracy requirements， the RecurDyn can be used to quickly and accurately obtain the fatigue life under dynamic loading， this fatigue performance research method provides a model and theoretical basis for the design and fatigue life analysis of worm and worm gear in the following automobile steering system.